Hubungan Hormon Dan Psikologi Pada Ibu Masa Perinatal - Marnisa, Fiiryal; Musfiroh, Sri; Triwahyuningsih, Ria Yulianti; Tonasih; Nabilah, Amatullah; Nur Aisyah, Zahra; Amalia, Rizki; angelina , Indri afni; Fransiska, Oilia (Jurnal Maternitas Kebidanan, 2023)
In this study the authors raised the title of "The Relationship of Hormones andPsychology in Perinatal Mothers". This study aims to review the journals that the authors havechosen. The method used in this study was a literature review of the 6,970 results that appeared, so a review was carried out on the 19 selected journals. The results of this study are that the relationship between hormones and psychology that occurs during the perinatal period is very complex and correlates with one another to support coping with the psychology felt by perinatal mothers. Understanding the emotional changes experienced by women during the perinatal period is very important to support appropriate care.